2017
DOI: 10.1063/1.4977449
|View full text |Cite
|
Sign up to set email alerts
|

Simulation study of a passive plasma beam dump using varying plasma density

Abstract: A plasma beam dump uses the collective oscillations of plasma electrons to absorb the kinetic energy of a particle beam. In this paper, a modified passive plasma beam dump scheme is proposed using either a gradient or stepped plasma profile to maintain a higher decelerating gradient compared to a uniform plasma. The improvement is a result of the plasma wavelength change preventing the re-acceleration of low energy particles. Particle-in-cell simulation results show that both stepped and gradient plasma profil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…After some time, the fraction of the bunch experiencing the maximum decelerating field will become non-relativistic, and it will fall behind the rest of the bunch until it reaches an accelerating phase of the wakefield. This causes beam re-acceleration, which eventually leads to saturation of beam net energy loss [9,13,14]. In order to eliminate beam re-acceleration, several schemes have been proposed, which include inserting foils in the plasma to absorb the re-accelerated particles, and tailoring the plasma density along the beam propagation direction to change the relative phases of wakefield along the beam driver.…”
Section: Plasma Beam Dumpsmentioning
confidence: 99%
See 1 more Smart Citation
“…After some time, the fraction of the bunch experiencing the maximum decelerating field will become non-relativistic, and it will fall behind the rest of the bunch until it reaches an accelerating phase of the wakefield. This causes beam re-acceleration, which eventually leads to saturation of beam net energy loss [9,13,14]. In order to eliminate beam re-acceleration, several schemes have been proposed, which include inserting foils in the plasma to absorb the re-accelerated particles, and tailoring the plasma density along the beam propagation direction to change the relative phases of wakefield along the beam driver.…”
Section: Plasma Beam Dumpsmentioning
confidence: 99%
“…In order to eliminate beam re-acceleration, several schemes have been proposed, which include inserting foils in the plasma to absorb the re-accelerated particles, and tailoring the plasma density along the beam propagation direction to change the relative phases of wakefield along the beam driver. Recent studies have shown that the beam energy deposition in plasma can be greatly enhanced through finely tailoring the plasma densities [13,14]. On the other hand, in the APBD this beam re-acceleration is eliminated.…”
Section: Plasma Beam Dumpsmentioning
confidence: 99%
“…After some time, the fraction of the bunch experiencing the maximum decelerating field will become non-relativistic, and it will fall behind the rest of the bunch until it reaches an accelerating phase of the wakefield. This causes beam re-acceleration, which eventually leads to saturation of the beam net energy loss [9,[13][14]. In order to eliminate the beam re-acceleration, several schemes have been proposed which include inserting foils in the plasma to absorb the re-accelerated particles, and tailoring the plasma density along the beam propagation direction to change the relative phases of wakefield along the beam driver.…”
Section: Plasma Beam Dumpsmentioning
confidence: 99%
“…In order to eliminate the beam re-acceleration, several schemes have been proposed which include inserting foils in the plasma to absorb the re-accelerated particles, and tailoring the plasma density along the beam propagation direction to change the relative phases of wakefield along the beam driver. Recent studies have shown that the beam energy deposition in plasma can be greatly enhanced through finely tailoring the plasma densities [13][14]. On the other hand, in the APBD this beam re-acceleration is eliminated.…”
Section: Plasma Beam Dumpsmentioning
confidence: 99%
“…Instead studies or ideas have been put forward for plasma colliders inspired or based on the parameter optimization done for CLIC and ILC, with the aim of improving certain parts of the machine. Examples are : adding an afterburner to an already built RF collider [11,12]; replacing injectors, possibly also damping rings and bunch compressors by plasma-based injectors [13]; improve/shorten the beam delivery system and final focus [14,15]; making beam dumps more compact, potentially with some energy recovery [16]; or, replacing the main linac with advanced accelerator technology. We will in this review focus on the latter, the main linac, since this part has been studied the most, and is the most costly component of the current collider design.…”
Section: Existing Collider Conceptsmentioning
confidence: 99%